2004
DOI: 10.1111/j.1523-1755.2004.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the tissue kallikrein promoter and transforming growth factor-β1 polymorphisms with renal progression in children with vesicoureteral reflux

Abstract: The K allele of KLK1 promoter and TT genotype of TGF-beta1 may be a genetic KLK1 -130 GN and -128 G-C, and the susceptibility factor contributing to progressive renal deterioration in Taiwanese primary VUR children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 18 publications
0
16
3
Order By: Relevance
“…Of these, 169 papers were excluded according to the inclusion and exclusion criteria. Nine studies 1,[10][11][12][13][14][15][16][17] were enrolled in our analysis for the association between TGF-b1 gene +869 T/C, À800 G/A, À509 T/C and +915 G/C polymorphisms and CKD risk (Figure 1). Among the enrolled nine studies, six for +869 T/C, one for À800 G/A, three for À509 T/C and five for +915 G/C (Figure 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 169 papers were excluded according to the inclusion and exclusion criteria. Nine studies 1,[10][11][12][13][14][15][16][17] were enrolled in our analysis for the association between TGF-b1 gene +869 T/C, À800 G/A, À509 T/C and +915 G/C polymorphisms and CKD risk (Figure 1). Among the enrolled nine studies, six for +869 T/C, one for À800 G/A, three for À509 T/C and five for +915 G/C (Figure 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Three studies 10,11,13 were identified for the analysis of the association between TGF-b1 gene À509 T/C polymorphism and CKD risk (Table 1). One study 13 was performed in Caucasians, and two 10,11 in Asians.…”
Section: Study Characteristics For Tgf-b1 Gene à509 T/c Polymorphism mentioning
confidence: 99%
See 2 more Smart Citations
“…Various genetic polymorphisms, including those within the TGF-β1 gene, are being increasingly recognized as factors influencing the progression of renal impairment. Early genetic association studies of TGF-β1 polymorphisms and renal impairment have reported conflicting results [17][18][19][20]. Consequently, the study reported here was designed to evaluate an association between the TGF-β1 gene polymorphisms rs1800469 and rs1982073 and primary vesicoureteral reflux or development of renal scarring in pediatric patients with VUR.…”
Section: Introductionmentioning
confidence: 95%